Penguatan Kapasitas Perawat melalui Pengabdian Masyarakat Berbasis Pelatihan Basic Trauma Cardiac Life Support - solehudin; Inas Syabanasyah; Cencen Hendra Setiawan; Imam Kurniawan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
Emergency services require nurses with the ability to respond quickly, accurately, and according to standards in handling trauma and cardiac arrest. One way to increase capacity is through Basic Trauma Cardiac Life Support (BTCLS) training. This community service program aims to improve nurses' skills and knowledge in handling emergency situations through BTCLS training. The implementation method uses a participatory-educational approach that includes preparation, pre-tests, theoretical presentations, skills demonstrations, case simulations, hands-on practice, and post-tests. The number of participants in the activity was 32 nurses from healthcare facilities. Evaluation was conducted by measuring knowledge and observing participants' skills before and after the training. The results of the activity showed that the average knowledge score of participants increased from 52.4 to 86.7 after the training. In addition, participants' skills in performing cardiopulmonary resuscitation, airway management, triage, and trauma management showed significant improvements. Participants also showed increased confidence when facing emergency situations. BTCLS training has been proven to be successful in improving nurses' abilities in the cognitive, affective, and psychomotor aspects. This program is expected to be implemented continuously as part of improving the quality of health services and patient safety